Visual cryptography and secret image sharing - Ching-Nung, Yang; Cimato, Stelvio (Digital imaging and computer vision, 2012)
"With rapid progress in Internet and digital imaging technology, there are more and more ways to easily create, publish, and distribute images. Considered the first book to focus on the relationship between digital imaging and privacy protection, Visual Cryptography and Secret Image Sharing is a complete introduction to novel security methods and sharing-control mechanisms used to protect against unauthorized data